Game theory approach to managerial strategies and value creation - Hammoudi, Abdelhakim; Daidj, Nabyla 1964- (Diverse and global perspectives on value creation set, 2018)
"Starting from strategic management problems and the case studies of the managerial school of thought, this book presents an original analysis of these problems based on concepts of game theory. A conceptual and operational approach to the resolution of these concrete problems (food industry, media, automation, energy) is proposed. The formulation of concepts is pedagogical with a perspective of operational use. The book covers both predictive and decision-making aspects of game theory and the reflexive dimension of theory. Through the tools presented, it helps to fine-tune the strategic decision-making process and to understand how a business strategy takes shape in a context of interactions and competition in the markets. Also discussed is the relationship between the company and public authorities in the context of corporate social responsibility (CSR)"--Back cover.